Selective detection of Fe3+, Cr3+ and Cu2+ in water using highly luminescent Gd2O3:Eu3+ nanoparticles - Ghosh, Debasish; Luwang, Meitram Niraj (Journal of Luminescence, 2016)
Rod shaped Eu3+ doped Gd2O3 nanoparticles were synthesised by a simple wet-chemical method followed by high temperature heating at 700 degrees C. The nanoparticles were characterised by X-ray diffraction (XRD), infra-red (IR), transmission electron microscopy (TEM), x-ray photonelectron spectroscopy (XPS), photoluminescence (PL) studies and lifetime measurement. The particles show strong host sensitised luminescence in water. Luminescence in water is selectively quenched by Fe3+, Cr3+ and Cu2+ ions. This luminescence quenching phenomenon has been utilised to detect metal ions in synthetic water and environmental water samples. Results obtained by luminescence quenching for environmental water samples are in good agreement with the results obtained from inductively coupled plasma atomic emission spectroscopy (ICP-AES) study. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Detection; Luminescence; Nanoparticles; Quenching; Sensitization

Synthesis of nanogate structure in GO-ZnS sandwich material - Kumar, Praveen; Luwang, Meitram Niraj (Scientific Reports, 2019)
Graphite Oxide (multi-layer) composite with other materials has a huge application in various field of science, due to its excellent and unique properties. Even though from past decade, immense research has been done by materials scientists in this field, but the chemistry is still not yet satisfactory. Here, in this work, through the discovery of Nanogate structure, we have reported for the first time the experimental results that enlightened the clear chemistry between the GO and ZnS which is further supported by the DFT calculations. This novel synthesis method led to the discovery of nanogate structure sandwiched between the GO layers. The nanogate formation also shows enhanced properties for various applications like photocatalytic activities, etc. Due to the nanogate formation, there might be a possibility of enormous generation of electrons on excitation of the composite materials, which can be a boom for various applications like photocatalysis, water splitting, solar cell, etc.

Sulfur functionalization via epoxide ring opening on a reduced graphene oxide surface to form metal (II) Organo-bis-[1,2]-oxathiin - Kumar, Praveen; Bajpai, Himanshu; Gopinath, Chinnakonda S.; Luwang, Meitram Niraj (Inorganic Chemistry, 2022)
The epoxide ring-opening reaction in graphene oxide (GO) by nucleophiles is a very fascinating and advanced methodology to develop novel functional material. Herewith, we report an advanced strategy for opening the epoxide ring on the rGO surface via easily an available nucleophile (Na2S), which is further functionalized with O atom to obtain four-membered rings (FMRs). The Cd coordination with the S atom puts extra stress on the FMR leading to the C-C bond cleavage of the four-membered heteroatomic rings on the rGO surface. This strategic approach leads to the fabrication of an innovative metal organo-bis-[1,2]-oxathiin (MOBOT) chemical moiety (M = Cd, Zn). The MOBOT compound further shows enhanced H-2 generation activity and hence is promising as a potential photocatalyst for solar hydrogen generation. This compound might also be a potential candidate for optoelectronic applications.